E0397 A correlational study of ACE gene polymorphisms. (17th November 2010) - Meiling, Yun; Yin, Zheng; Jianghua, Zhong; Yu, Zeng; Tianfa, Li; Yong, Zhang
Abstract : Objective: To study the correlation of the ACE gene polymorphisms with coronary heart disease (CHD) in the Hainan Li nationality. Methods: Used the PCR to detect the polymorphisms of ACE gene insertion/deletion (I/D) in 150 patients with CHD and 150 healthy people from Hainan Li nationality. The genotype frequencies and allele frequencies of DD, DI and II were observed. Specific PCR detection was performed for patients who have been determined as DD by normal PCR to reduce misclassification rate. Results: In the CHD group of Hainan Li nationality, the genotype frequencies of DD, DI and II were 24.7%, 32.7%, 42.6% respectively, and the allele frequencies of D and I were 41.0% and 59.0%. In the healthy control of Hainan Li nationality, the genotype frequencies of DD, DI and II were 14.0%, 44.0%, 42.0% respectively, and the allele frequencies of D and I were 36.0% and 64.0%. There were significant differences both in the genotype frequencies of DD, DI and II, and in allele frequencies D and I between these two groups (p<0.05). There were no significant differences in the age, the blood pressure, the body mass index (BMI), the total serum cholesterol (TC) and the low density lipoprotein cholesterol (LDL-C) between these two groups (p>0.05). There was significant differences in the sex between these two groups (p<0.05). The triglyceride (TG) level in the CHD group was significantly higher than in the control(p<0.05). The high density lipoprotein cholesterol (HDL-C) level in the CHD group was significantly lower than the control (p<0.05). Conclusions: There were notable correlation between the ACE gene I/D polymorphisms and the CHD in Hainan Li nationality. The ACE gene polymorphisms are the major gene that causes CHD in Hainan Li nationality. It may be the independent risk factor in CHD in Hainan Li nationality. So it is very important to intervene with ACEI inhibitors or angiotensin receptor blockers (ARB) in the early stage of CHD.